Speech Acts in Minangkabau Language during Commercial Transactions in Mentawai’s Traditional Market: A Case Study in Pasar Raya Muara Siberut - Pratiwi, Anne; Revita, Ike; Fauzanna, Wulan; Ghaniyyah, Miftahul; Amri, Ulil (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2025)
This descriptive-qualitative research aims to analyze the forms of speech acts that use the Minangkabau language for commercial transactions in Mentawai’s traditional market. The data were extracted from natural communication in Pasar Raya Muara Siberut, Mentawai Islands. This research focuses on identifying the five types of illocutionary acts: assertive, directive, commissive, expressive, and declarations. The result shows that assertive and commissive are the most dominant types, reflecting the transactional nature of the interactions. The other forms, expressive, are used to maintain harmony, while directives appear less frequently but serve specific purposes in agreement and decision-making. In addition, the declaration speech acts were not found during the transaction. This study highlights how cultural values and local norms shape the pragmatic use of language in the traditional market, especially in using the Minangkabau language.